Conformal organic–inorganic semiconductor composites for flexible thermoelectrics. Issue 2 (22nd January 2020) - Xu, Qing; Qu, Sanyin; Ming, Chen; Qiu, Pengfei; Yao, Qin; Zhu, Chenxi; Wei, Tian-Ran; He, Jian; Shi, Xun; Chen, Lidong
Abstract : The development of flexible organic–inorganic thermoelectric composites constitutes a promising material approach toward harvesting heat from the human body or environment to power wearable electronics. Abstract : The development of flexible organic–inorganic thermoelectric composites constitutes a promising material approach toward harvesting heat from the human body or environment to power wearable electronics. To this end, compositing one-dimensional inorganic materials, such as carbon nanotubes or metal nanowires, with organic polymers has demonstrated efficacy but also drawbacks: e.g., the Seebeck coefficient of an inorganic constituent is too low to meet the onset voltage requirement of electronics, and it is hard to attain coherent interfaces between the inorganic and organic constituents. Here, we proposed a dimensionality/morphology matching strategy and conducted a proof-of-principle study on (PVDF)/Ta4 SiTe4 organic–inorganic composites. A record high normalized maximum power density of 0.13 W m −1 at a temperature difference of 35.5 K was obtained in prototype flexible thermoelectric modules made of (PVDF)/Ta4 SiTe4 composites. This study attests to the efficacy of the dimensionality/morphology matching strategy and the potential of using such conformal semiconducting organic–inorganic composites in wearable electronics.